Pengaruh Leverage, Pertumbuhan Penjualan, dan Capital Intensity terhadap Tax Avoidance - Arya Thresna H.S; Andrea Titania Chalissa; Hera Dini Fauziah; Pungki Atma Negara (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Tax avoidance can be interpreted as an activity to minimize the tax burden that must be issued by the taxpayer. This study aims to determine the effect of leverage, sales growth, and capital intensity on tax avoidance in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period partially or simultaneously. The population in this study were Property and Real Estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. The sample selection technique used purposive sampling and obtained 45 companies in the Property and Real Estate sub-sector within 4 years. years so that 180 samples were observed. The method of data analysis in this study is panel data regression using Eviews software.